Vascular Semaphorin 7A Upregulation by Disturbed Flow Promotes Atherosclerosis Through Endothelial β1 Integrin. Issue 2 (February 2018) - Hu, Shuhong; Liu, Yifei; You, Tao; Heath, Jack; Xu, Linru; Zheng, Xiaowei; Wang, Aili; Wang, Yinyan; Li, Fengchan; Yang, Fei; Cao, Yiren; Zhang, Huayu; et al.
Abstract : Objective—: Accumulating evidence suggests a role of semaphorins in vascular homeostasis. Here, we investigate the role of Sema7A (semaphorin 7A) in atherosclerosis and its underlying mechanism. Approach and Results—: Using genetically engineered Sema7A −/− ApoE −/− mice, we showed that deletion of Sema7A attenuates atherosclerotic plaque formation primarily in the aorta of ApoE −/− mice on a high-fat diet. A higher level of Sema7A in the atheroprone lesser curvature suggests a correlation of Sema7A with disturbed flow. This notion is supported by elevated Sema7A expression in human umbilical venous endothelial cells either subjected to oscillatory shear stress or treated with the PKA (protein kinase A)/CREB (cAMP response element-binding protein) inhibitor H89 ( N -[2-(p-bromocinnamylamino)ethyl]-5-isoquinolinesulfonamide·2HCl hydrate). Further studies using the partial carotid artery ligation model showed that disturbed flow in the left carotid artery of Sema7A +/+ ApoE −/− mice promoted the expression of endothelial Sema7A and cell adhesion molecules, leukocyte adhesion, and plaque formation, whereas such changes were attenuated in Sema7A −/− ApoE −/− mice. Further studies showed that blockage of β1 integrin, a known Sema7A receptor, or inhibition of FAK (focal adhesion kinase), MEK1/2 (mitogen-activated protein kinase kinase 1/2), or NF-κB (nuclear factor-κB) significantly reduced the expression of cell adhesion molecules and THP-1 (human acute monocytic leukemia cell line) monocyte adhesion in Sema7A-overexpressing human umbilical venous endothelial cells. Studies using chimeric mice suggest that vascular, most likely endothelial, Sema7A plays a major role in atherogenesis. Conclusions—: Our findings indicate a significant role of Sema7A in atherosclerosis by mediating endothelial dysfunction in a β1 integrin–dependent manner. Abstract : Supplemental Digital Content is available in the text.